Multimedia Annotation: An Unsuccessful Tool Becomes a Successful Framework - Grudin, Jonathan; Bargeron, David (Communication and Collaboration Support Systems, 2005)
We designed and deployed a conceptually simple multi-media annotation tool called the Microsoft Research Annotation System. We expected it to be widely useful in education settings with little or no modification. In a series of deployments over three years we encountered a surprising range of specific interface requirements. We ultimately shifted from an application focus to a platform focus, from a single general-purpose tool to a toolkit to support asynchronous group interaction. Software that can be widely used with little or no modification has advantages for producers and consumers, but as computer users become more aware of the flexibility of software, general purpose shrinkwrap software may fade away. We discuss implications for designers, developers, and users. In addition, our experiences publishing our results pointed to a tendency to favor initial descriptions of success and reject deeper analysis of failure, a practice that is likely to inhibit progress in systems research.